Spatial-Temporal Performance Variability of 1 kWp Polycrystalline PV Systems across Indonesia’s Diverse Climate Zones - MUHAMMAD IRSAN; NURUL CHAIRUNNISA NOOR; MUHAMMAD HAFIS (ELKOMIKA: Jurnal Teknik Energi Elektrik, Teknik Telekomunikasi, & Teknik Elektronika, 2026)
Indonesia has enormous solar energy potential, but local climate variability often causes deviations between design estimates and actual performance. This study aims to analyze the effect of climate parameters on the performance of a 1 kWp solar power system in six different climate zones through PVsyst simulation. The results show significant variations in annual energy production, with the highest values in Makassar (1,453 kWh/kWp) and Ternate (1,452 kWh/kWp), while the lowest is in Jakarta (1,293 kWh/kWp). This difference is triggered by the diffuse radiation (DIF) ratio, which reaches 1,001.4 kWh/m² in Jakarta due to pollution and high cloud cover, which reduces the Performance Ratio (PR) to an average of 76%. This study concludes that microclimate factors, particularly the DNI/DIF ratio, are more decisive for system efficiency than daily average radiation alone.